Analisis Faktor Agresivitas Pajak Sebelum dan Masa Pandemi Covid19 - Santikah, Amanda; Nurul Azizah, Siti; Uzliawati, Lia (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Tax aggressiveness is an activity aimed at reducing taxable profits through tax planning, either using methods that are in accordance with regulations or not in accordance with tax regulations. This research was conducted to examine the effect of corporate social responsibility (CSR), leverage, profitability, company size on tax aggressiveness. The research population is mining companies listed on the Indonesia Stock Exchange, with samples taken of 43 financial statements of mining companies for 2016-2020. Data analysis used the regression analysis model using IBM SPSS 25 software. The results showed that profitability and firm size had a positive effect on tax aggressiveness.